Identification of knowledge cores on a competence graph of project managers - Гогунський, Віктор Дмитрович; Лук’янов, Дмитро Володимирович; Власенко, Олена Вікторівна (Eastern-European Journal of Enterprise Technologies, 2012)
The theoretical justification the formation of core competence of project managers on the basis of the characteristic properties of the adjacency matrix and its powers is offered